The Effectiveness of Contextual Teaching Learning Through Zoom in Improving Arabic Speaking Skills During Covid-19 - Rosita Ilhami; Nur Hasan; Wildana Wargadinata; Muhammad Fadhlan; Ahmad Fikri (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
This study aims to determine the effectiveness of the contextual teaching learning (CTL) method through zoom in improving Arabic speaking skills during Covid-19. This type of research is quantitative research with an experimental approach using a series of research the one-group pretest-posttest design. The object of this research was the 3rd-semester students of Islamic Education at the State Islamic Institute Kerinci. The research technique was carried out using tests and observations. The results showed that the significance value of 0.000 <probability 0.05 then Ho is rejected and Ha is accepted. Also, there is a significant difference in the mean learning outcomes between the pretest and posttest with the mean paired differences of -18,500. These results indicate the average learning outcomes between pretest and posttest 59.56 - 78.06 = -18,500 and the difference between these differences is between -20,618 to -16,382. From these results, it was explained that the contextual teaching learning (CTL) method through zoom was effective in improving the Arabic speaking skills of 3rd-semester students of Islamic Education at the State Islamic Institute Kerinci.